Manajemen Pendidikan Dan Pelatihan Kepemimpinan Administrator Di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Kalimantan Tengah - Ajatul, Ajatul; Musyarafah, Musyarafah; Riyadi, Slamet (Jurnal Media Informatika, 2025)
The process of developing human resources, especially ASN, has again undergone changes, this is certainly inseparable from the challenges that arise at this time. One way to improve the quality of human resources, especially ASN, is through education and training activities. Administrator leadership education and training activities are one of the activities carried out to improve the competence of ASN with the rank of echelon III. This study aims to determine the management of administrator leadership education and training at BPSDM Central Kalimantan Province. The research is descriptive with a qualitative approach. The results showed that the planning of administrator leadership education and training at BPSDM Central Kalimantan Province was organized through several stages. The stages carried out start from coordination meetings, budgeting, preparation, participants, teachers, organizing teams and facilities. Similarly, the implementation is carried out through several stages. Implementation stages carried out starting from the opening of activities, training materials and curriculum, general lectures, Pancasila leadership agenda, performance leadership agenda, performance management agenda, leadership actualization agenda, field study agenda, change action preparation agenda, change action design seminar agenda, actualization of change, change action report seminar and closing of administrator leadership training activities. This shows that BPSDM Central Kalimantan Province in organizing activities is very careful and pays attention to all aspects. This certainly has an impact on the effectiveness and success of organizing administrator leadership education and training activities within the Central Kalimantan Province.